Penerapan Terapi Bermain Puzzle Dalam Menurunkan Ansietas Pada Anak yang Dihospitalisasi dengan Kejang Demam - Annisa Rosiana; Siti Nurhayati (AKPER Pasar Rebo, 2023)
The application of puzzle play therapy can minimize anxiety in children undergoing hospitalization. The implementation of puzzle play therapy in nursing care for children with febrile seizures who experience anxiety is carried out through a comprehensive nursing process approach. The descriptive method was chosen with a case study approach accompanied by the application of evidence-based practice. The results of the application of nursing care were carried out on a male patient, aged 3 years, with a medical diagnosis of simple febrile seizure. Analysis of the assessment data found two main problems, namely anxiety and hypovolemia. The application of 5 minutes of puzzle play therapy with a frequency of 2x/day for three days has been proven to be able to reduce children's anxiety levels. The final evaluation results showed that there was a decrease in the level of anxiety from a scale of 8 to 2 on the third day. In conclusion, puzzle games can be applied to pediatric patients with febrile seizures to decrease anxiety. The nurse's suggestion is to apply playing puzzles to minimize anxiety with varying game difficulty levels and a wider age range